2001
DOI: 10.2307/3558334
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography and origin of Lilium longiflorum and L. formosanum (Liliaceae) endemic to the Ryukyu Archipelago and Taiwan as determined by allozyme diversity

Abstract: Allozyme diversity on 13 isozyme loci was investigated for two bulbous species, Lilium longiflorum and L. formosanum, endemic to the subtropical archipelago of continental origin located in East Asia. Degrees of allozyme variability and divergence for L. longiflorum were very high for insular endemic species, indicating relatively longtime persistence of the present widespread distribution across many islands in this phenotypically little-changed species. Lilium formosanum exhibited rather lower variability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 57 publications
3
63
0
Order By: Relevance
“…Since L. formosanum is a derivative of L. longiflorum (Hiramatsu et al, 2001a), lack or reduction of bulb dormancy with early flowering ability is the result of adaptation to southern climate conditions from a heavy dormancy trait in L. longiflorum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since L. formosanum is a derivative of L. longiflorum (Hiramatsu et al, 2001a), lack or reduction of bulb dormancy with early flowering ability is the result of adaptation to southern climate conditions from a heavy dormancy trait in L. longiflorum.…”
Section: Discussionmentioning
confidence: 99%
“…Based on genetic and morphological analyses, L. formosanum and L. longiflorum populations have a close relationship (Nishikawa et al, 2001), and it has been confirmed by allozyme analysis that L. formosanum is a derivative of L. longiflorum. L. formosanum shows early onset of flowering among Lilium species (Hiramatsu et al, 2001a). It is considered that this trait was obtained by shifting the anthesis time to late summer to ensure firstyear biomass accumulation (Saruwatari, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although its cultivars have been used as a suitable plant material to study the SI reaction mechanism Peloquin, 1966, 1970;Li et al, 1996;Matsubara, 1973;Suzuki et al, 2001;Tezuka et al, 2007;van Tuyl et al, 1982), selfcompatible individuals and cultivars had never been discovered. Recently, Hiramatsu et al (2001a) revealed that genetic variability and divergence in L. longiflorum are very high, and that isozyme loci with a significant excess of homozygous genotypes frequently occur in some natural populations. Self-fertilization by selfcompatible individuals has been suggested as a potential cause of homozygous excesses.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to distinguish these species by leaf morphology, flowering time, and habitat (Hiramatsu et al, 2001b). Hiramatsu et al (2001a) suggested that L. formosanum is a derivative of L. longiflorum populations at the southern edge of the species distribution based on the data from allozyme diversity. Multiple transitions from SI dominance to SC dominance may have occurred in L. longiflorum populations.…”
Section: Introductionmentioning
confidence: 99%
“…Sea-level changes during the Pleistocene glacials were also responsible for the composition of species around the coasts and the continental islands of East Asia and the genetic diversity of species, including, for example, gobioid fishes in the northeastern Pacific coasts (Fu et al, 2010), lilies in Taiwan and Ryukyus (Hiramatsu et al, 2001), the genus Kirengeshoma in East China and South Korea and Japan , and monkeys in China, Japan, and Taiwan (Wu et al, 2007). The varied diversification rate through the time period of Clade 3 (Figure 2) that primarily encompassed the East Asian continental islands (Taiwan and Japan) was probably a consequence of repeated fragmentation and secondary contacts of populations between the islands (Japan and Taiwan) and the continent (China) during the Pleistocene glacial oscillations.…”
Section: Diversification Rate Shift and Biogeographic Inferencementioning
confidence: 99%